Implementasi Model Problem Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa pada Materi Sumber-Sumber Energi di Kelas X J SMAN 2 Pamekasan - Maysarotul Sholehah; Suprianto; S. Ida Kholida MS; Mabruratul Hasanah; Lukluk Ibana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Abstract: This study aims to improve students' problem-solving abilities through the application of the Problem-Based Learning (PBL) model in the energy resources curriculum for grades 10 X-J at SMAN 2 Pamekasan. This study uses a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, which includes the stages of planning, action, observation, and reflection. The research subjects consisted of 33 students involved in two learning cycles, with each cycle carried out in one session for 3 × 45 minutes. Data collection was carried out through observation, testing, and documentation. The testing instrument was designed based on Polya's problem-solving ability indicators, namely understanding the problem, formulating a plan, implementing the plan, and reviewing the results. Data analysis used a quantitative descriptive method to test the development of students' skills in each cycle. The results showed an increase in problem-solving abilities after the application of PBL, as evidenced by an increase in the average score from 81.15 in the pre-cycle to 96.20 in Cycle I and 97.03 in Cycle II. The percentage of learning completion also increased from 63.64% in the pre-cycle to 93.94% in the first cycle and reached 97% in the second cycle. Thus, it can be concluded that the PBL model is effective in improving students' problem-solving abilities in physics learning.